2014
DOI: 10.1016/j.jalz.2014.04.256
|View full text |Cite
|
Sign up to set email alerts
|

F3‐02‐01: Cognitive Impairment Precedes and Predicts Functional Impairment in Mild Alzheimer's Disease

Abstract: Abstract.Background: The temporal relationship of cognitive deficit and functional impairment in Alzheimer's disease (AD) is not well characterized. Recent analyses suggest cognitive decline predicts subsequent functional decline throughout AD progression. Objective: To better understand the relationship between cognitive and functional decline in mild AD using autoregressive cross-lagged (ARCL) panel analyses in several clinical trials. Methods: Data included placebo patients with mild AD pooled from two mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
5
2
Order By: Relevance
“…Our finding that the functional component of the CFC detected clinical progression whereas the cognitive component did not, may seem counterintuitive as the assumed clinical trajectory of AD entails that cognitive impairment induces and thereby precedes functional impairment [48]. However, our findings do not argue against this conceptual understanding of cognitive impairment preceding functional change, but rather imply that existing paper-andpencil cognitive tests may not provide the right tools to capture subtle cognitive decline.…”
Section: Discussioncontrasting
confidence: 73%
“…Our finding that the functional component of the CFC detected clinical progression whereas the cognitive component did not, may seem counterintuitive as the assumed clinical trajectory of AD entails that cognitive impairment induces and thereby precedes functional impairment [48]. However, our findings do not argue against this conceptual understanding of cognitive impairment preceding functional change, but rather imply that existing paper-andpencil cognitive tests may not provide the right tools to capture subtle cognitive decline.…”
Section: Discussioncontrasting
confidence: 73%
“…Our finding of a significant between-group difference in functional decline but not cognitive decline over 36 months was unexpected given that studies of disease progression in patients with mild AD have suggested that cognitive decline generally precedes and predicts functional decline (25). Possible reasons for this include that patients in the GERAS and EXPEDITION cohorts in this study had an MMSE score of ~23 at baseline (towards the middle of the mild MMSE score spectrum [21][22][23][24][25][26]) and would probably have progressed to moderate cognitive decline (MMSE score <20) within 3 years; solanezumab, as a disease-modifying drug, was shown to have no effect on cognition in patients with moderate AD dementia in the EXPEDITION studies (8). Also, although patients in the GERAS study received treatment as part of standard care, this treatment may have been more rigorously applied than usual because they were participating in the study.…”
Section: Discussioncontrasting
confidence: 53%
“…Patients with Mini-Mental Status Examination (MMSE) scores of 16-26 were eligible to participate. 15 Mild AD was defined as screening visit MMSE scores of 20-26; moderate AD was defined as screening visit scores of [16][17][18][19]. Patients were allowed to continue treatment with stable doses of standard-of-care AD treatments throughout the studies.…”
Section: Methodsmentioning
confidence: 99%